Analisis Penerapan Akuntansi Lingkungan pada PT. Perkebunan Nusantara IV Regional II Balimbingan - Sipayung, Tasya Krista Winda; Thomas Sumarsan Goh; Apriani Magdalena Sibarani (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2026)
This study aims to examine the implementation of environmental accounting and to analyze the level of effectiveness and efficiency of its implementation at PT Perkebunan Nusantara IV Regional II Balimbingan. The research employed a descriptive method with qualitative and quantitative approaches. Data were collected through interviews, documentation, and the company’s financial reports. The effectiveness was measured using a weighted checklist method, while efficiency was analyzed using ratio analysis. The results indicate that the implementation of environmental accounting at PT Perkebunan Nusantara IV Regional II Balimbingan has been carried out through the stages of identification, recognition, measurement, presentation, and disclosure of environmental costs. Based on the weighted assessment of all indicators, the effectiveness level reached 93%, which falls into the very effective category. Furthermore, the efficiency analysis shows that the environmental cost ratio of 73.64% reflects the company’s ability to control environmental expenditures according to the allocated budget, the environmental activity efficiency of 71.43% indicates that most environmental programs have been implemented, and the waste-to-production volume ratio of 11.43% suggests that waste management still needs improvement to achieve optimal performance.